Dificulties in teaching English pronunciation to 11-form student at Yen Vien High school and possible solutions = - Trần, Thị Thu Giang (University of Foreign Languages and International Studies, 2017)
Role of pronunciation in oral communication and foreign language learning. An overview of new English textbook "Tieng Anh 11" and the current situatio of teaching the textbook at Yen Vien High School. Proposed solutions.